3PL Shipping Company Vendor Selection Model for Nickel Ore Processing Companies - Ferdy Adityawan; Iwan Vanany (International Journal Labs, 2026)
The nickel ore processing industry requires an efficient supply chain system to ensure production continuity and global competitiveness, especially in the distribution of raw materials to smelting facilities. One of the main problems faced by companies is the selection of Third-Party Logistics (3PL) vendors, which has not fully considered quality, performance, and safety aspects comprehensively. This study aims to analyze the selection of the most optimal 3PL vendor in supporting the effectiveness of the supply chain in nickel ore processing companies. The research method used is a quantitative approach based on Multi-Criteria Decision-Making (MCDM) with the integration of the Analytic Hierarchy Process (AHP) and VIKOR methods. AHP is used to determine the weight of six criteria and fifteen sub-criteria, while VIKOR is used to conduct the alternative ranking of 3PL vendors. The results showed that the quality and safety criteria carry a higher weight than price, which confirms the importance of the total cost of quality approach in logistics decision-making. PT A is recommended as the best vendor alternative based on the lowest VIKOR index value. This study concludes that the selection of the right 3PL vendor has a significant effect on the supply chain effectiveness of the nickel ore processing industry.